Analisis Proksimat Madu Kelulut (Heterotrigona itama) dari Kelurahan Palam Banjarbaru Kalimantan Selatan - Fikri, Hendriannur; Satriadi, Trisnu; Mahdie, Muhammad Faisal (Universitas Lambung Mangkurat, 2024)
ABSTRACT. Kelulut bees that produce honey are one of the non-timber forest products that are rich in benefits. The content contained in kelulut bee honey has a positive impact on health if used properly. The purpose of this study was to analyze the proximate content of kelulut honey including protein, water, fat, ash, carbohydrate and calorie content. The honey samples used came from the Palam Banjarbaru Urban Village honey farm and proximate testing was carried out at the Lambung Mangkurat University Faculty of Medicine laboratory Biokomia. The research method used a quantitative approach and data analysis using a descriptive-quantitative approach. The results of the proximate analysis of kelulut honey can be seen that the content in kelulut honey samples is 28.92% water content, 0.18% ash content, 0.45% protein content, 0.03% fat content, 70.36% carbohydrate content and 285.26 for calorie test.ABSTRAK. Lebah kelulut yang menghasilkan madu merupakan salah satu hasil hutan bukan kayu yang kaya akan manfaat. Kandungan dalam madu lebah kelulut memberikan dampak positif bagi kesehatan jika dipergunakan dengan tepat. Tujuan penelitian ini untuk menganalisis kandungan proksimat madu kelulut meliputi uji kadar protein, air, lemak, abu, karbohidrat dan kalori. Sampel madu yang digunakan berasal dari peternakan madu Kelurahan Palam Banjarbaru serta pengujian proksimat dilakukan di Labolatorium Biokimia Fakultas Kedokteran Universitas Lambung Mangkurat. Metode penelitian menggunakan pendekatan kuantitatif dan analisis data menggunakan pendekatan deskriftif–kuantitatif. Hasil analisis proksimat madu kelulut dapat diketahui bahwa kandungan yang ada pada sampel madu kelulut yaitu 28.92 % Kadar Air ,0,18 % kadar abu, 0,45 % kadar protein, 0,03% kadar lemak, 70,36 % kadar karbohidrat dan 285,26 untuk uji kalori.